2013
DOI: 10.1097/cji.0b013e3182943549
|View full text |Cite
|
Sign up to set email alerts
|

Long-lasting Complete Regression of Established Mouse Tumors by Counteracting Th2 Inflammation

Abstract: Mice with intraperitoneal ID8 ovarian carcinoma or subcutaneous SW1 melanoma were injected with monoclonal antibodies (mAbs) to CD137+PD-1+CTLA4 7-15 days following tumor initiation. Survival of mice with ID8 tumors tripled and >40% of mice with SW1 tumors remain healthy >150 days after later treatment and are probably cured. Therapeutic efficacy was associated with a systemic immune response with memory and antigen specificity and required CD4+ cells and involved CD8+ cells and NK cells to a less extent. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
75
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(85 citation statements)
references
References 47 publications
8
75
0
2
Order By: Relevance
“…1). The combination of anti-4-1BB with anti-PD-1 was also more efficacious than dual combinations of anti-CLTA-4/anti-PD-1 and anti-4-1BB/anti-CTLA-4 in the ID8 model (16,17). Therefore, in at least two of the most aggressive and poorly immunogenic tumor models (ID8 and B16), anti-4-1BB/ anti-PD-1 combination appears to exhibit the strongest antitumor effect among the dual-agent combinations of several widely studied pathways (CTLA-4, PD-1, LAG-3, and 4-1BB).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…1). The combination of anti-4-1BB with anti-PD-1 was also more efficacious than dual combinations of anti-CLTA-4/anti-PD-1 and anti-4-1BB/anti-CTLA-4 in the ID8 model (16,17). Therefore, in at least two of the most aggressive and poorly immunogenic tumor models (ID8 and B16), anti-4-1BB/ anti-PD-1 combination appears to exhibit the strongest antitumor effect among the dual-agent combinations of several widely studied pathways (CTLA-4, PD-1, LAG-3, and 4-1BB).…”
Section: Discussionmentioning
confidence: 95%
“…Synergistic antitumor effects have been observed for combinations of anti-4-1BB with anti-TIM-3 (15) or with anti-PD-1 (16,17) in the ID8 murine ovarian cancer model. Studies on ID8 ovarian carcinoma also indicated that the anti-4-1BB/anti-PD-L1 combination had moderate impact on survival, which could be further improved with additional vaccination (18).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Preclinical data suggest that combined targeting of costimulatory and inhibitory immune checkpoint pathways may enhance antitumor immune responses and prolong survival and could reduce the incidence of immune-mediated AEs, including liver inflammation (16,(24)(25)(26). In summary, urelumab at 0.1 mg/kg every 3 weeks is well tolerated with evidence of immunologic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that B cell depletion results in an increased tumor growth, 50 although it has also been shown, as in our case, to enhance survival in combination with checkpoint inhibitors. 51 …”
Section: Discusionmentioning
confidence: 99%